U.S.-KYRGYZSTAN: PARTNERS IN DIFFERENT WEIGHT DIVISIONS - KAZAKPAEV, Marat (CENTRAL ASIA AND THE CAUCASUS, 2006)
As soon as Kyrgyzstan became an independent state, its relations with the United States in the military-political sphere moved ahead at a slack pace mainly because the “island of democracy,” as the country was perceived in Central Asia, was too small and too poor economically to be contemplated as a strategic partner first by the Clinton and later by the George W. Bush Administration. However, the Kyrgyz Republic’s consistent and positive foreign policy with respect to the U.S. contributed to the positive dynamics of their bilateral relations in all spheres. Thus, in the military-political sphere, all related government structures, the Defense Ministry in particular, invariably took part (with Washington’s support) in all of the West’s military-political events and profited from all types of military-technical aid extended by the U.S. and/or the EU.Bilateral military-political contacts developed within NATO as well: as soon as Kyrgyzstan and NATO signed the Partnership for Peace Program with the White House’s direct support on 1 June,1994, Kyrgyzstan had the opportunity to take part in NATO’s other important programs. The U.S. strengthened its position across the post-Soviet expanse when Kyrgyzstan (in December 1997), as well as other CIS countries, joined the Euro-Atlantic Partnership Council (EAPC). This was highly conducive to its effective cooperation with NATO members, the U.S. in particular, in the international and regional security sphere. America pays the lion’s share to the two countries’ joint military planning and Kyrgyzstan’s defense budget. By the end of 2005, annual foreign military aid to Kyrgyzstan’s security system topped $8 million.NATO and the United States as its member initiated other measures within the Partnership for Peace Program. A peacekeeping battalion Centrazbat was set up; its activities included annu-al training exercises and multi-national non-military projects. The latter included the Virtual Silk Highway, which would give all academic and educational establishments Internet access, and Coping with Ecological Problems for the Sake of the Central Asian Countries Sustainable Devel-opment. Since 1999, the Defense Ministry of the Kyrgyz Republic has been involved in two purely American programs (Military Activities in Mountains and Special Purpose Forces) implemented outside NATO.The 9/11 events began another phase of American foreign policy and military activities in relation to the Taliban, which Washington accused of being directly involved in the terrorist act. Central Asia found itself in the center of new developments which launched another and probably qualitatively new stage of political relations between Central Asia and the United States. In other words, 9/11 and the counterterrorist operation of the international coalition forced the George W. Bush Administration to revise its former foreign policy ideas about Afghanistan’s Central Asian neighbors. They became part of America’s geopolitical priorities.